Determinants of home delivery in a semi urban setting of Nepal - Tuladhar, Heera (Nepal Journal of Obstetrics and Gynaecology, 2010)
Aim: To study the effect of various determinants of home delivery in Nepal. Methods: Prospective descriptive study among women who after being delivered at home were admitted in Nepal Medical College Teaching Hospital (NMCTH), a tertiary care hospital situated at suburban area of Kathmandu Results: Of 114 women, majority were between the ages of 20-24 yrs. Most of the women were multipara (64%). Majority had no formal education accounting for 68.4 %. Lasheta (Lama, Sherpa , Tamang) was the most common ethnic group. Most (30.1%) of their spouses also were illiterate or had only primary level education. Majority of the husbands of the respondents were laborers (63.2%). Regarding attendance of antenatal care (ANC); at least 84 (73.7%) women had attended ANC once and half of the women had attended 4 more visits. Home delivery was planned by 67 (58.8%) women; whereas only 47 (41.2%) had chosen hospital delivery and delivered at home due to various reasons. Financial problem was the most common reason followed by ignorance and transportation problem. Among all the women, only 5.3% were attended to by a professionally trained provider (doctor, nurse, and midwife). A disturbingly high proportion of women (87.6%) were attended by an untrained family member, friend or neighbor, and 7% of women delivered completely unattended. Women were brought to the hospital by family member 59.6% other than husband and 8.8% were accompanied by neighbors/friends. Most of these women were brought with retained placenta, primary post partum hemorrhage. Conclusion: In this study area, usage of the antenatal care was high, but the opportunity to deliver at hospital was not fully utilized. This study has highlighted some of the factors affecting the choice of place of delivery among mothers in a semi urban settlement in Nepal namely mothers educational level, husband's education and occupation, financial constraints, lack of transportation and ignorance. Majority of the deliveries took place at home and unsupervised by a skilled attendant thus aggravating the risk of the high perinatal and maternal morbidities and mortalities in the study area. Key words: Home delivery; determinants; antenatal care; delivery attendance DOI: 10.3126/njog.v4i1.3329 Nepal Journal of Obstetrics and Gynaecology June-July 2009; 4(1): 30-37